Impact of Personality, Behavior and Attitudes on Company Worker Psychology: A Critical Analysis (International Journal of Food and Nutritional Sciences, 2022)
Psychology is the science that studies the experiential behavior of humans and non-human animals.Psychology is the scientific study of behavior and mental processes. Personalities are characterized in terms oftraits, which are relatively durable characteristics that influence our behavior in many situations. Personalitytraits such as introversion, friendliness, honesty, integrity, and helpfulness are important because they helpexplain behavioral consistency. Another aspect of personality that influences work is friendship. Those whoexcel in this trait are cooperative, understanding and empathetic. Their influence on their environment isusually very positive because they understand others easily. Some social interactions are based on socialprocesses such as adjustment, opposition and cooperation. Social psychology can also be said to be the sciencethat studies the relationships and processes involved in social interactions